Tissue-Resident Macrophages in the Stria Vascularis - Ito, Taku; Kurata, Natsuko; Fukunaga, Yoko (Frontiers in Neurology, 2022)
Tissue-resident macrophages play an important role in the clearance, development, and regulation of metabolism. They also function as sentinel immune cells, initiating inflammatory responses, clearing inflammatory debris, and maintaining homeostatic tissue environments. Specifically, in the cochlea, the roles of tissue-resident macrophages include: maintaining steady state tissues, immunological defense, and repairing the pathological conditions associated with noise, ototoxic drugs, aging, and various pathogens. Perivascular macrophages (PVMs) are a unique subset of tissue-resident macrophages characterized by a close association with blood vessels and particular expression makers in certain tissues. PVMs are found in the inner ear, brain, skin, liver, and retina. The origin of PVMs in the inner ear is unclear; but, PVMs are already present during embryonic development. PVMs are a member of the blood labyrinth barrier and regulate blood vessel permeability in the stria vascularis, which lies on the lateral wall of the cochlear duct and is crucial for the formation of the endocochlear potential. The cytoplasm of strial PVMs can contain pigment granules, the number and amount of which are more frequent with age. Strial PVMs are activated with the loss of Slc26a4 in cochleae and subsequently phagocytose parts of aggregated pigmentation, and possibly degenerated intermediate cells. This review summarizes reported currently known characteristic features and proposed roles of PVMs in the stria vascularis. Additionally, we address macrophage activation and involvement with pigment granules observed in the loss of Slc26a4 in cochleae.